Volume 8: Turbomachinery, Parts A, B, and C 2012
DOI: 10.1115/gt2012-68707
|View full text |Cite
|
Sign up to set email alerts
|

Origins and Structure of Spike-Type Rotating Stall

Abstract: In this paper we describe the structures that produce a spike-type route to rotating stall and explain the physical mechanism for their formation. The descriptions and explanations are based on numerical simulations, complemented and corroborated by experiments. It is found that spikes are caused by a loss of pressure rise capability in the rotor tip region, due to flow separation resulting from high incidence. The separation gives rise to shedding of vorticity from the leading edge and the consequent formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 15 publications
3
39
0
Order By: Relevance
“…The interface between the streamwise inflow and with tip clearance flow is aligned with the leading edge plane. This is consistent with the explanation [24] and also recently confirmed by Weichert et al [25] and Pullan et al [26]. The similarity predicted in this study is due to the design of this rotor, some blades encounter higher incidence beyond the critical value near the tip region which leads to separations from the suction side.…”
Section: Rotating Stall For Undamaged Assemblysupporting
confidence: 81%
See 1 more Smart Citation
“…The interface between the streamwise inflow and with tip clearance flow is aligned with the leading edge plane. This is consistent with the explanation [24] and also recently confirmed by Weichert et al [25] and Pullan et al [26]. The similarity predicted in this study is due to the design of this rotor, some blades encounter higher incidence beyond the critical value near the tip region which leads to separations from the suction side.…”
Section: Rotating Stall For Undamaged Assemblysupporting
confidence: 81%
“…[ 26], who predicted a radial vortex starting from the blade's leading edge at the suction side which could be due to the different compressor blade design used in their analysis where the blades have lower hub to tip ratio and thus rotor blades have much less twist near the tip than Rotor 37. are not shown here to avoid repetition. it showed that the non-rotating stall cell was caused by the damaged blade because the flow was always diverted by the damage feature at the leading edge.…”
Section: Rotating Stall For Undamaged Assemblymentioning
confidence: 99%
“…Recent numerical and experimental works converge towards explaining the typical increase and decrease in wall pressure by a vortex structure forming at the leading edge of the rotor blade and spanning to the casing ("tornado vortex"). Inoue et al [3] identified this numerically at first, and recent numerical and experimental works by Pullan et al [4] support those results. In high-speed compressors, the spike type structure evolves very quickly (a few rotor revolutions) into a rotating stall cell.…”
Section: Introductionsupporting
confidence: 56%
“…At 100% shaft speed, the typical increase and decrease related to a spike type perturbation are found [4]. The increase and decrease of the static pressure extend each over four rotor blade passing instances (not detailed here).…”
Section: Global Overviewmentioning
confidence: 99%
“…At approximately revolution 0, a single stall cell or spike begins to form and rotate around the annulus. A static pressure rise occurs upstream of the blade row similar to Pullan et al [18], which extends over the span of multiple blade passages. Initially, the trailing edge of the stall cell rotates at a rate of 0.71N and slows down in the laboratory frame as the stall cell increased in circumferential size.…”
Section: Leading Edge Shroud Static Pressure Time Seriesmentioning
confidence: 89%